Exploring Links between Geology, Hydroperiod, and Diversity and Distribution Patterns of Anostracans and Notostracans (Branchiopoda) in a Tropical Savannah Habitat in SE Zimbabwe. Issue 3 (1st May 2015) - Brendonck, Luc; Clegg, Bruce; Nhiwatiwa, Tamuka; Tuytens, Karen; Vanschoenwinkel, Bram
Abstract: Southern Africa is recognized as one of the world's diversity hotspots for large branchiopod crustaceans. Nonetheless, many areas including large parts of Zimbabwe remain poorly studied. We report on the diversity of anostracans and notostracans in a tropical and geologically diverse savannah area in SE Zimbabwe. We explored the links between geology, hydroperiod and diversity and distribution patterns of anostracans and notostracans. In a large survey, 160 temporary clay pans distributed over the four major and diverse geological regions were sampled every fortnight. Seven fairy shrimp and one tadpole shrimp species were recorded. Although the study area is characterized by substantial variation in soil geology, we did not find strong effects of geology on the composition of anostracan and notostracan assemblages in pools of different sizes and hydrology. All species occurred in all four geological regions but the abundance of pools without large branchiopods differed between the four investigated regions.